Ferret airway epithelial cell cultures support efficient replication of influenza B virus but not mumps virus. - Roberts, Kim (My University, 2015)
Ferrets have become the model animal of choice for inﬂuenza pathology and transmission experiments as they are permissive and susceptible to human inﬂuenza A viruses. However, inoculation of ferrets with mumps virus (MuV) did not lead to successful infections. We evaluated the use of highly differentiated ferret tracheal epithelium cell cultures, FTE, for predicting the potential of ferrets to support respiratory viral infections. FTE cultures supported productive replication of human inﬂuenza A and B viruses but not of MuV, whereas analogous cells generated from human airways supported replication of all three viruses. We propose that in vitro strategies using these cultures might serve as a method of triaging viruses and potentially reducing the use of ferrets in viral studies.
PUBLISHED
Keywords: influenza viruses; influenza pathology; ferrets; Immunology, Inflammation & Infection; INFLUENZA; Molecular Biology